Donor‐Node‐Acceptor Type Hole‐Transporting Materials Based on Conjugated Polymers with Perylene Diimide Pendants for High‐Performance Vertical‐Structure Perovskite Photodetectors. Issue 20 (19th July 2022) - Wang, Hailong; Zhang, Qinglei; Zhou, Jiadong; Su, Xiaojun; Xie, Guojing; Tang, Ningning; Zheng, Nan; Liu, Linlin; Xie, Zengqi
Abstract: A series of donor‐node‐acceptor (D‐n‐A) type polymers containing linear conjugated backbone as donor and various contents of tetrachloronated perylene diimide (4Cl‐PDI) pendant as acceptor are synthesized for the application as hole‐transporting layers (HTLs) in n‐i‐p structured perovskite photodetectors (PDs). The strong aggregation behaviors of the linear conjugated backbone endow the polymers excellent hole transporting properties, and the strong electron affinity of 4Cl‐PDI pendant enables easily trapping of free electrons. Besides, the 4Cl‐PDI pendants in polymers suppress the intrinsic face‐on orientation of conjugated backbone. Both of the electron‐trapping property of 4Cl‐PDI pendant and the favorable edge‐on orientation of the conjugated backbone are benefits for restraining the dark current in perovskite PDs. Based on such D‐n‐A type hole‐transporting materials, durable vertical‐structure perovskite PDs are successfully demonstrated with superior performance of high responsivity of 0.32 A W −1, high detectivity of 2.2 × 10 12  Jones, and fast response speed in microsecond scales. Abstract : Donor‐node‐acceptor (D‐n‐A) type polymers containing linear conjugated backbone as donor and various contents of tetrachloronated perylene diimide (4Cl‐PDI) pendant as acceptor are used as hole‐transporting layers in perovskite photodetectors. The small amount of 4Cl‐PDI combined with conjugated backbone possesses good electron‐blocking ability, photo‐induced charge transfer as well as suppressed face‐on orientation, which are favorable for enhancing the detectivity.